(untitled) (Indian Journal of Arid Horticulture, 2025)
The experiment conducted at farmers’ fields in Bikaner district on sandy soil during the Kharif season of 2003 and 2004 under canal command area for crop diversification in different fruit-based cropping systems revealed that the maximum plant height of mothbean and groundnut was recorded under the intercropping with Bael, whereas the maximum plant height (49.8 cm) of clusterbean was observed under intercropping with Ber. Mothbean intercropped with Bael produced 14.61% and 27.24% higher total dry matter (26.99 q/ha) and grain yield (10.40 q/ha), respectively, compared to intercropping with Ber (23.77 and 8.98 q/ha). Among the entire intercrop, the highest mean root dry matter addition (2.49 q/ha) to soil after crop harvest was observed in groundnut intercropping, which was significantly higher than mothbean and clusterbean intercroppings. However, the mean highest system productivity (8.71 q/ha) was observed under groundnut intercropping with fruit trees, which was 15.09% and 9.82% higher than the intercropping of mothbean and clusterbean, respectively. The highest total income (Rs. 35,172/ha), net profit (Rs. 30,162/ha), and cost-benefit ratio (6.02) were observed under the intercropping systems of Bael + Mothbean.